2016
DOI: 10.1016/j.jcma.2016.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of combined vitrectomy and transscleral suture fixation of posterior chamber intraocular lenses in the management of posteriorly dislocated lenses

Abstract: Our data showed that use of combined vitrectomy and transscleral suture fixation of PC IOLs is a safe and efficient technique to correct aphakia in eyes without adequate capsular support. Our study demonstrated good long-term visual outcome with only minor complications. Furthermore, we recommend that the IOL power should be adjusted 1.00 D less for transscleral suture fixation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
2
9
0
1
Order By: Relevance
“…6 The overall postoperative refractive outcomes from our study appear to be superior to those previously reported for sulcus-fixated IOLs using Prolene. 17 Furthermore, the mean postoperative manifest refraction was also similar to previous literature reports. 17,18 The final refraction tends to be more myopic because sulcus-fixated IOLs are more anterior compared with in-the-bag placement.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…6 The overall postoperative refractive outcomes from our study appear to be superior to those previously reported for sulcus-fixated IOLs using Prolene. 17 Furthermore, the mean postoperative manifest refraction was also similar to previous literature reports. 17,18 The final refraction tends to be more myopic because sulcus-fixated IOLs are more anterior compared with in-the-bag placement.…”
Section: Discussionsupporting
confidence: 88%
“…17 Furthermore, the mean postoperative manifest refraction was also similar to previous literature reports. 17,18 The final refraction tends to be more myopic because sulcus-fixated IOLs are more anterior compared with in-the-bag placement. However, because a hyperopic shift was found in a few cases, we suggest that a target refraction of -0.5 to -1.0 D is optimal.…”
Section: Discussionsupporting
confidence: 88%
“…Following PPV, patients have numerous available option for secondary visual rehabilitation from the aphakia. In absent or insufficient of capsular support, IOL may be sutured to the sclera (transscleral suture fixation) or iris, exchanged for an AC IOL or using aphakic spectacle or contact lens correction 5,10 .…”
Section: Discussionmentioning
confidence: 99%
“…Most common postoperative complication of the refixation or exchange IOL is decrease of ECD. AC IOL implantation for low ECD patient is avoided because potential complication related to AC IOL may be a gradual decrease of ECD 10 . Kristianlund et al in their study found postoperative significant ECD loss of 10% in IOL exchange group than nonsignificant 3% ECD loss in repositioning group at 6 th month follow-up 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Zarówno w przypadku soczewek iris-claw, jak i implantów fiksowanych do twardówki opisane zostały powikłania po-operacyjne obejmujące m.in. : przemieszczenie implantu, wzrost ciśnienia wewnątrzgałkowego, krwawienie do ciała szklistego, torbielowaty obrzęk plamki (CME, cystoid macular edema) czy odwarstwienie siatkówki [9][10][11][12][13][14]. Z uwagi na nieskomplikowaną technikę oraz stosunkowo krótki czas zabiegu wielu chirurgów preferuje implanty iris-claw w korekcji bezsoczewkowości z uszkodzoną obwódką rzęskową lub torebką tylną [15,16]…”
unclassified